2D GeP as a Novel Broadband Nonlinear Optical Material for Ultrafast Photonics. Issue 9 (12th August 2019) - Guo, Jia; Huang, Dazhou; Zhang, Yue; Yao, Huizhen; Wang, Yunzheng; Zhang, Feng; Wang, Rui; Ge, Yanqi; Song, Yufeng; Guo, Zhinan; Yang, Fumei; Liu, Jiefeng; et al.
Abstract: A new member of the IV–V compounds, germanium–phosphorus (Ge–P) compounds, has been shown in experiment and theory to have a tunable bandgap ( E g ), excellent chemical stability, strong in‐plane anisotropy, and wide‐range optical absorption, all indicating a promising future in electronic and optoelectronic applications. In this work, the application potential of Ge–P compounds as nonlinear optical (NLO) materials in ultrafast photonics is studied for the first time. The strong light–matter interaction, broad and tunable Ep, and broadband and strong optical response make GeP a likely NLO material for photonics, especially in infrared photonic devices. In addition, 2D GeP nanosheets are mixed with poly(vinylidene fluoride) (PVDF) to obtain a GeP@PVDF composite film, which further improves the stability of the GeP and, for the development of organic photonic devices, helps to slow its degradation. From Z‐scan data and fitting results, it is found that GeP has an excellent broadband NLO response. Moreover, using the GeP@PVDF composite film as a saturable absorber, a high‐stability femtosecond laser with a 722 fs pulse width is obtained in the telecommunications band. Preliminarily, Ge–P compounds display excellent optical properties suggesting that they may be used as NLO materials in advanced photonic devices. Abstract : 2D GeP nanosheets are fabricated by liquid‐phase exfoliation. By mixing the 2D GeP nanosheets with poly(vinylidene fluoride) (PVDF), uniform GeP@PVDF composite films are obtained. The morphology, optical absorption, chemical stability, and nonlinear optical properties are investigated. Employing the GeP@PVDF composite film as a saturable absorber, a highly stable femtosecond laser is obtained.